Installation of cladding / Muhammad Hafiz Danial Razelan - Razelan, Muhammad Hafiz Danial (Universiti Teknologi MARA, Perak, 2014)
This report covers almost all matters regarding the Installation of Cladding by explaining the materials used method of installation, differences with other finishes, pros and contras, and the maintenance to ensure that the cladding will stand for a few years. In addition, the information gained through about 5 months industrial practical training at AMG LRT line extension Station 1 that is situated at Bukit Jalil. The content of the report is arranged by stating the company profile followed by case study of installation of cladding. The report explained more detail on the sequence of method of installation, material used, and differences with other external finishes. Overall, this report focuses on main information related to Installation of Cladding as external finishes.